Modelling Hollow Microneedle-Mediated Drug Delivery in Skin Considering Drug Binding - Tanmoy Bhuimali; Sarifuddin; Diganta Bhusan Das; Prashanta Kumar Mandal (Pharmaceutics)
Background/Objectives: Microneedle(MN)-based drug delivery is one of the potential approaches to overcome the limitations of oral and hypodermic needle delivery. An in silico model has been developed for hollow microneedle (HMN)-based drug delivery in the skin and its subsequent absorption in the blood and tissue compartments in the presence of interstitial flow. The drug’s reversible specific saturable binding to its receptors and the kinetics of reversible absorption across the blood and tissue compartments have been taken into account. Methods: The governing equations representing the flow of interstitial fluid, the transport of verapamil in the viable skin and the concentrations in the blood and tissue compartments are solved using combined Marker and Cell and Immersed Boundary Methods to gain a quantitative understanding of the model under consideration. Results: The viscoelastic skin is predicted to impede the transport of verapamil in the viable skin and, hence, reduce the concentrations of all forms in the blood and the tissue compartments. The findings reveal that a higher mean concentration in the viable skin is not always associated with a longer MN length. Simulations also predict that the concentrations of verapamil in the blood and bound verapamil in the tissue compartment rise with decreasing tip diameters. In contrast, the concentration of free verapamil in the tissue increases with increasing injection velocities. Conclusions: The novelty of this study includes verapamil metabolism in two-dimensional viscoelastic irregular viable skin and the nonlinear, specific, saturable, and reversible binding of verapamil in the tissue compartment. The tip diameter and the drug’s injection velocity are thought to serve as regulatory parameters for the effectiveness and efficacy of MN-mediated therapy if the MN is robust enough to sustain the force needed to penetrate a wider tip into the skin.